2011
DOI: 10.1128/jvi.00572-11
|View full text |Cite|
|
Sign up to set email alerts
|

The Human Cytomegalovirus Protein pUL38 Suppresses Endoplasmic Reticulum Stress-Mediated Cell Death Independently of Its Ability To Induce mTORC1 Activation

Abstract: As obligate intracellular parasites, viruses not only hijack cellular machinery, they also deregulate host stress responses for their infection. Human cytomegalovirus (HCMV) modulates the endoplasmic reticulum (ER) stress response, due at least in part to the viral protein pUL38, and one of the consequences is to maintain the viability of infected cells. Consequently, pUL38-deficient virus induces premature cell death during infection. In addition, pUL38 activates mammalian target of rapamycin complex 1 (mTORC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 40 publications
2
39
0
Order By: Relevance
“…Therefore, we determined if the N-terminal-truncated mutants of pUL38 retained the ability to activate mTORC1. We used S6K phosphorylation (phos-S6K) as an indicator of mTORC1 activation, as described previously (31). The ADpmUL38 mutant virus induced apparent S6K phosphorylation, consistent with our previous report that HCMV could activate mTORC1 in a pUL38-independent manner (31).…”
Section: Construction and Analysis Of Serial N-terminal-truncated Mutmentioning
confidence: 49%
See 3 more Smart Citations
“…Therefore, we determined if the N-terminal-truncated mutants of pUL38 retained the ability to activate mTORC1. We used S6K phosphorylation (phos-S6K) as an indicator of mTORC1 activation, as described previously (31). The ADpmUL38 mutant virus induced apparent S6K phosphorylation, consistent with our previous report that HCMV could activate mTORC1 in a pUL38-independent manner (31).…”
Section: Construction and Analysis Of Serial N-terminal-truncated Mutmentioning
confidence: 49%
“…However, the mechanisms whereby pUL38 interacts with TSC2 to activate mTORC1 are unclear. We previously showed that the N-terminal 239 residues of pUL38 were necessary and sufficient to block premature cell death but were unable to activate mTORC1 in isolation, demonstrating that cell death inhibition by pUL38 was independent of its mTORC1 activation domain (31). In the present study, we further defined the TSC2-binding motif of pUL38 and showed that a TSC2-binding-deficient pUL38 mutant still was able to activate mTORC1.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…The infective full-length HCoV-OC43 cDNA clone pBAC-OC43-WT was kindly provided by Pierre J. Talbot (INRS-Institut Armand-Frappier, Québec, Canada). The pBAC-OC43-⌬ns12.9 cDNA clone was constructed in our laboratory by following a previously described protocol (29). Briefly, a cassette containing a stop codon at the fourth amino acid of the ns12.9 gene followed by the sequence with a selective kanamycin marker flanked by flippase recognition target (FRT) sites was amplified from the pYD-C191 plasmid with a pair of 70-nucleotide (nt) primers as the following primers: OC43-FRT-F (forward), 5=-CTAGCATTTGTTAAAGTTCTTAAGGCCACGC CCTATTAATGGACATTTGAAAGGACGACGACGACAAGTAA-3=; O C43-FRT-R (reverse), 5=-TCTGAGACATTAAAACCGTTAATATAA CGGAGATATTTCTTCTCAGGTCTACCACGTCGTGGAATGCC TTC-3=.…”
Section: Cells and Virusesmentioning
confidence: 99%